2015
DOI: 10.1200/jco.2015.33.7_suppl.372
|View full text |Cite
|
Sign up to set email alerts
|

A single-arm, multicenter, open-label phase II trial of cabazitaxel as second-line treatment for patients with locally advanced or metastatic transitional cell carcinoma (TCC).

Abstract: 372 Background: For patients with advanced TCC who have progressed on a platinum-based regimen, no widely accepted standard second line therapy currently exists. A 2-stage phase II study was conducted to assess the activity and toxicity profile of the microtubule inhibitor cabazitaxel (Jevtana; FDA-approved in hormone-refractory metastatic prostate cancer previously treated with a docetaxel-containing regimen) in patients with metastatic TCC after failure of prior platinum-based chemotherapy. ClinicalTrials.g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…[ 74 ] Cabazitaxel in Phase 2 studies has shown 5% ORR but with increased toxicity and is currently being trialed as the second-line agent. [ 75 ] The initial Phase 2 study with pemetrexed reported a promising OS of 9.6 months;[ 76 ] however, more recent studies of pemetrexed reported a low ORR of 5%–8% with median PFS of 2.4 months. [ 77 78 ] Gemcitabine has been tested in three Phase 2 trials, with RR of up to 29%, median survival 9–13 months, and better median survival if administered in weekly for 3 weeks every 28 days.…”
Section: Methodsmentioning
confidence: 99%
“…[ 74 ] Cabazitaxel in Phase 2 studies has shown 5% ORR but with increased toxicity and is currently being trialed as the second-line agent. [ 75 ] The initial Phase 2 study with pemetrexed reported a promising OS of 9.6 months;[ 76 ] however, more recent studies of pemetrexed reported a low ORR of 5%–8% with median PFS of 2.4 months. [ 77 78 ] Gemcitabine has been tested in three Phase 2 trials, with RR of up to 29%, median survival 9–13 months, and better median survival if administered in weekly for 3 weeks every 28 days.…”
Section: Methodsmentioning
confidence: 99%